Feasibility of Administering High‐Dose 131I–MIBG Therapy to Children with High‐Risk Neuroblastoma Without Lead‐Lined Rooms. Issue 5 (15th January 2016) - Chu, Bae P.; Horan, Christopher; Basu, Ellen; Dauer, Lawrence; Williamson, Matthew; Carrasquillo, Jorge A.; Pandit‐Taskar, Neeta; Modak, Shakeel
Abstract : Background: Although 131 I–metaiodobenzylguanidine ( 131 I–MIBG) therapy is increasingly used for children with high‐risk neuroblastoma, a paucity of lead‐lined rooms limits its wider use. We implemented radiation safety procedures to comply with New York City Department of Health and Mental Hygiene regulations for therapeutic radioisotopes and administered 131 I–MIBG using rolling lead shields. Procedure: Patients received 0.67 GBq (18 mCi)/kg/dose 131 I–MIBG on an IRB‐approved protocol (NCT00107289). Radiation safety procedures included private room with installation of rolling lead shields to maintain area dose rates ≤0.02 mSv/hr outside the room, patient isolation until dose rate <0.07 mSv/hr at 1 m, and retention of a urinary catheter with collection of urine in lead boxes. Parents were permitted in the patient's room behind lead shields, trained in radiation safety principles, and given real‐time radiation monitors. Results: Records on 16 131 I–MIBG infusions among 10 patients (age 2–11 years) were reviewed. Mean ± standard deviation 131 I–MIBG administered was 17.67 ± 11.14 (range: 6.11–40.59) GBq. Mean maximum dose rates outside treatment rooms were 0.013 ± 0.008 mSv/hr. Median time‐to‐discharge was 3 days post‐ 131 I–MIBG. Exposure of medical staff and parents was below regulatory limits. Cumulative whole‐body dose received by the physician, nurse, and radiation safety officer during treatment was 0.098 ± 0.058, 0.056 ± 0.045, 0.055 ± 0.050 mSv, respectively. Cumulative exposure to parents was 0.978 ± 0.579 mSv. Estimated annual radiation exposure for inpatient nurses was 0.096 ± 0.034 mSv/nurse. Thyroid bioassay scans on all medical personnel showed less than detectable activity. Contamination surveys were <200 dpm/100 cm 2 . Conclusions: The use of rolling lead shields and implementation of specific radiation safety procedures allows administration of high‐dose 131 I–MIBG and may broaden its use without dedicated lead‐lined rooms.